2015
DOI: 10.3389/fmicb.2015.00536
|View full text |Cite
|
Sign up to set email alerts
|

Spread of tetracycline resistance genes at a conventional dairy farm

Abstract: The use of antibiotics in animal husbandry contributes to the worldwide problem of increasing antibiotic resistance in animal and human pathogens. Intensive animal production is considered an important source of antibiotic resistance genes released to the environment, while the contribution of smaller farms remains to be evaluated. Here we monitor the spread of tetracycline resistance (TC-r) genes at a middle-size conventional dairy farm, where chlortetracycline (CTC, as intrauterine suppository) is prophylact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
58
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 39 publications
9
58
1
1
Order By: Relevance
“…(59%), NAS (34%), and Klebsiella spp. (32%), similar to a previous report for China (Yassin et al, 2017) and consistent with spread of tetracycline-resistance genes on a conventional dairy farm (Kyselková et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…(59%), NAS (34%), and Klebsiella spp. (32%), similar to a previous report for China (Yassin et al, 2017) and consistent with spread of tetracycline-resistance genes on a conventional dairy farm (Kyselková et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…These findings are in agreement with the results by Thames et al, (2012), Agga et al (2015), Gerzova et al (2015), Iweriebor et al (2015), Madoshi et al (2016) and Pitta et al (2016) who reported high presence of tetC, tetG, tetO, tetW, and tetX in their studies. The findings are also similar to the results reported by Kyselkova et al (2015) when studying the occurrence of tetracycline resistance genes at conventional dairy farm. However, Englen et al (2006) reported that Campylobacter jejuni displayed tetracycline and nalidixic acid resistance genes while C. coli indicated resistance to azithromycin, ciprofloxacin, clindamycin, erythromycin, gentamicin, and tetracycline from cow fecal isolates.…”
Section: Blaaccsupporting
confidence: 90%
“…The observed transmission of resistance genes through contaminated cow and calf bedding and soil (Call et al, 2013; Kyselková et al, 2015; Liu et al, 2016), highlights the importance of biosecurity and the need to separate animals being treated for infection from the herd (where feasible), and not reusing bedding from infected and treated animals (Mitchell et al, 2015). Intramuscular treatment of healthy calves with ceftiofur or florfenicol, as per manufacturer’s recommendations, was shown to be sufficient to establish a reservoir of drug-resistant Escherichia coli in the feces, soil and bedding of treated animals (Liu et al, 2016).…”
Section: Drivers Of Resistance: Antibioticsmentioning
confidence: 99%
“…The dissemination of these materials on soil increases the ARG exposure risk to: (1) (wild) animals; (2) crops; (3) adjacent surface water bodies; (4) groundwater; (5) farm workers; and (6) air as dust particles from land spreading or aeolian erosion (Heuer et al, 2011; Ferro et al, 2015; Kyselková et al, 2015). The persistence and changes in the ‘resistome’ [the collection of genes that are capable of conferring resistance toward antibiotics when expressed in a susceptible organism (Dantas and Sommer, 2012)] of sludge or manure after it is anaerobically digested or composted is only recently emerging.…”
Section: Relevance Of Amr To Environmental Regulators?mentioning
confidence: 99%